ショウワ キチ ト カクコク キチ ノ イリョウ ノ ヒカク タイセイ,シボウレイ,キンキュウ ハンシュツ ノ ケントウ - 大野, 義一朗; オオノ, ギイチロウ; 宮田, 敬博; ミヤタ, タカヒロ; Ohno, Giichiro; Miyata, Takahiro (2000)
P(論文) 1998年9月, 越冬中の各国基地医師にファックス, 電子メールを送り医療現状調査をおこない昭和基地と比較した。7基地から直接回答があり10ヵ国14基地の情報を収集した。医師数は日本隊が2名で他は1名であった。医師以外の医療従事者がいるのは1基地のみ。手術室のある基地は多いが実際に手術を行っている基地は少ない。集計死亡数76件のうち病死9%, 事故死72%, 不明19%。病死では急性心疾患が最多で, 事故死の73%が航空機事故だった。日本隊の死亡1名は実数でも比率でも少ない。その理由は隊員選抜の健康診断が有効に機能していてこれまで致命的な疾患が発生していないことと, 大陸間航空路がなく航空機関連事故が起きていないためと考えられる。昭和基地でも重症患者の救命に不可欠な緊急搬出用航空路をどのようにして安全に導入するかが課題である。 In September of 1998,we sent questions about base medical systems to Antarctic wintering team doctors by facsimile and e-mail and we obtained information about 14 stations of 10 nations. Syowa has two doctors. Most other stations have one. Only one has paramedical workers. Many stations have an operation room but only few operations have been done. There have been 76 deaths : 9% from disease, 72% from accidents and 19% from unknown causes. The major fatal disease was the heart attack, 73% of fatal accident involved airplanes and helicopters. The very low mortality of Syowa may be because effective personnel selection avoids severe disease and there are no severe accidents by intercontinental aircraft. The problem is how JARE can establish an indispensable air-evacuation system safely. departmental bulletin paper